2007
DOI: 10.1097/ajp.0b013e31802fc14a
|View full text |Cite
|
Sign up to set email alerts
|

Patient Compliance With SSRIs and Gabapentin in Painful Diabetic Neuropathy

Abstract: The lack of negative effects on quality of life, the better compliance, and the comparable efficiency of SSRIs suggest that these drugs may be considered as alternative to gabapentin in painful diabetic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 13 publications
0
27
0
3
Order By: Relevance
“…Future research should therefore investigate determinants of underuse and overuse non-adherence separately. Overuse of medication was not taken into account in the study of Giannopoulos et al (2007). Our own research (Broekmans et al, unpublished results) showed that irrespective of pain diagnosis, these two types of non adherence are present.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should therefore investigate determinants of underuse and overuse non-adherence separately. Overuse of medication was not taken into account in the study of Giannopoulos et al (2007). Our own research (Broekmans et al, unpublished results) showed that irrespective of pain diagnosis, these two types of non adherence are present.…”
mentioning
confidence: 99%
“…There are no studies on how adherent patients have to be to ensure positive outcomes. Giannopoulos et al (2007) used a cut off of 75% to define adherence: patients taking less than 75% of their medication were considered non-adherent. However, the authors did not report on outcome differences between adherent and non-adherent patients.…”
mentioning
confidence: 99%
“…(51). Similarmente, tantos as DAE tradicionais como as de nova geração têm sido utilizadas na neuropatia diabética, que atinge de 40% a 50% dos pacientes com diabetes melito em algum momento da evolução da doença (51)(52)(53). Nos quadros sintomáticos, as DAE constituem uma boa opção terapêutica, frequentemente associadas aos antidepressivos tricíclicos, que são as drogas de primeira linha na abordagem da neuropatia diabética.…”
Section: Dae E Função Tireoideanaunclassified
“…Ela é geralmente bem tolerada e apresenta bons resultados, os quais podem ser aumentados quando em associação com a amitriptilina (51)(52)(53)56). Inicia-se o tratamento com a dose de 300 mg/dia e aumenta-se semanalmente até atingir uma dosagem entre 900 e 1800 mg, fracionada em três administrações.…”
Section: Dae E Função Tireoideanaunclassified
“…Several studies have shown that Selective Serotonin Reuptake Inhibitors (SSRIs) also have potential analgesic effects, but this effect is lower than that of the TCAs (Giannopoulos et al, 2007;Varia et al, 2000). Because they are associated with fewer side effects however, they have recently started to replace TCAs in the treatment of chronic pain (Miller and Rabe-Jablonska, 2005).…”
Section: Introductionmentioning
confidence: 99%